2023
DOI: 10.3389/fpls.2022.1037972
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of intrinsic water-use efficiency from δ13C signature of C3 leaves: Assumptions and uncertainty

Abstract: Carbon isotope composition (δ13C) has been widely used to estimate the intrinsic water-use efficiency (iWUE) of plants in ecosystems around the world, providing an ultimate record of the functional response of plants to climate change. This approach relies on established relationships between leaf gas exchange and isotopic discrimination, which are reflected in different formulations of 13C-based iWUE models. In the current literature, most studies have utilized the simple, linear equation of photosynthetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Similar results have been reported in young olive trees exposed to long-term eT (+4°C) (Miserere et al, 2021), suggesting an inevitable water loss in trees under eT. Moreover, uncertainty regarding the estimation of WUEi from δ 13 C existed due to the potential interferences with mesophyll conductance to CO 2 and postphotosynthetic fractionation (Ma et al, 2023). A study with Eucalyptus tereticornis also reported the difference in mesophyll conductance between the whole-tree and leaf scales as well as the necessity of incorporating mesophyll conductance to 13 C-based WUEi model (Gimeno et al, 2021).…”
Section: Different Scales Of Wue Response To Climate Change In Forest...supporting
confidence: 80%
“…Similar results have been reported in young olive trees exposed to long-term eT (+4°C) (Miserere et al, 2021), suggesting an inevitable water loss in trees under eT. Moreover, uncertainty regarding the estimation of WUEi from δ 13 C existed due to the potential interferences with mesophyll conductance to CO 2 and postphotosynthetic fractionation (Ma et al, 2023). A study with Eucalyptus tereticornis also reported the difference in mesophyll conductance between the whole-tree and leaf scales as well as the necessity of incorporating mesophyll conductance to 13 C-based WUEi model (Gimeno et al, 2021).…”
Section: Different Scales Of Wue Response To Climate Change In Forest...supporting
confidence: 80%
“…iWUE is regarded as an important functional property of plant ecosystems and a key determinant in the response of regional and global carbon, water, and energy cycles to climate change (19,20). Retrospective assessment of iWUE across large spatiotemporal scales relies on Δtrc analysis (1-5) which, in turn, relies on the assumption that DR discrimination governs Δtrc variability (6,11,21). However, DR discrimination accounts for merely ≈17.6% of the total variance of Δglu during the late period while PR discrimination accounts for ≈45.4% (Fig.…”
Section: Components Of δGlu Variation and Implications For Reconstruc...mentioning
confidence: 99%
“…From this material, five aboveground and three belowground functional traits related to water and nutrient acquisition were measured (see functional roles in Table 1): Leaf Dry Matter Content (LDMC; leaf dry mass per unit of water-saturated fresh mass; mg g -1 ), Specific Leaf Area (SLA; leaf area per unit of leaf dry mass; m 2 kg -1 ), leaf carbon isotopic composition (d 13 C; ‰), leaf carbon to nitrogen ratio (leaf C:N), Stem Dry Matter Content (SDMC; stem dry mass per unit of watersaturated fresh mass; mg g -1 ), Huber value (Hv; sapwood crosssectional branch area to supported leaf area ratio; cm 2 cm -2 ), Specific Root Area (SRA; root area per unit of root dry mass; m 2 kg -1 ), average root diameter (Rdi; mm), and root C:N ratio (root C:N). Leaf d 13 C is a proxy of intrinsic water use efficiency (iWUE, Prieto et al, 2018;Ma et al, 2023). The Huber value reflects the mass investment in xylem area with respect to leaf area (Mencuccini et al, 2019); it is thus a measure of how species adjust their leaf and sapwood areas to water supply (Carter and White, 2009;Zhang et al, 2019) and is related to groundwater depth extraction (Carter and White, 2009).…”
Section: Plant Sampling and Trait Measurementsmentioning
confidence: 99%